Persepsi Masyarakat Tentang Subsidi Langsung Tunai (Studi Kasus Penanggulangan Kemiskinan Di Kel. Bukit Biru Kec. Tenggarong) - Novianto, Efri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
Poorness is the very complex problem so after that never been dry from the dicussion. The poorness problem are verry complexed there for cannot be seen by partial or is only seen in by one side and furgetting the othen side. Inclueding of also in the case of solution. Some wrong decision in poorness solution not merely affecting undiminished impecunious sosiety perception of about direct cash subsidies in poornes handling. The research approach used by writer in this research is qualitative descriptive. Tehnique analysis used follow what opened by miles and huberman that it interaktive tehnique analysis; reduce the data, presentation of data and conclusion result of research. Society perseption on of direct cash subsidies the resource person majority express not objection with the existence of the policy. While at the time that society expectation to government in overcoming poorness in chief of Bukit Biru Village is the government do the small society enableness (for example through counselling program, education, training and capital employed gift) repairing the transportation acces so that can lessen the fare produce and open the new employment. Key word : Perception